The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/ece3.4672
|View full text |Cite
|
Sign up to set email alerts
|

Range‐wide genomic data synthesis reveals transatlantic vicariance and secondary contact in Atlantic cod

Abstract: Recent advances in genetic and genomic analysis have greatly improved our understanding of spatial population structure in marine species. However, studies addressing phylogeographic patterns at oceanic spatial scales remain rare. In Atlantic cod (Gadus morhua), existing range‐wide examinations suggest significant transatlantic divergence, although the fine‐scale contemporary distribution of populations and potential for secondary contact are largely unresolved. Here, we explore transatlantic phylogeography in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 78 publications
4
6
0
Order By: Relevance
“…Nevertheless, these estimates should be interpreted cautiously given that deviation from the mutation rate that we used here may substantially alter demographic parameter estimates (although the ratio of estimated time of secondary contact over divergence time still applies). Overall, our results are consistent with an increasing recent report of secondary contact in a wide range of marine species such as the European anchovy (Le Moan et al, 2016), the Atlantic cod (Gadus morhua; Fairweather et al, 2018) and European sea bass (Dicentrarchus labrax; Tine et al, 2014).…”
Section: Physical Separation Followed By Secondary Contacts Explainsupporting
confidence: 93%
“…Nevertheless, these estimates should be interpreted cautiously given that deviation from the mutation rate that we used here may substantially alter demographic parameter estimates (although the ratio of estimated time of secondary contact over divergence time still applies). Overall, our results are consistent with an increasing recent report of secondary contact in a wide range of marine species such as the European anchovy (Le Moan et al, 2016), the Atlantic cod (Gadus morhua; Fairweather et al, 2018) and European sea bass (Dicentrarchus labrax; Tine et al, 2014).…”
Section: Physical Separation Followed By Secondary Contacts Explainsupporting
confidence: 93%
“…and differentiation evolved in situ [5,42,43]. A major genetic divide is between the eastern Baltic Sea population and all other populations, with a genetic shift of allele frequencies overlapping with the steepest part of the salinity gradient (Figure 2).…”
Section: The Nature Of Barrier Mechanismsmentioning
confidence: 99%
“…In the North Sea (International Council for the Exploration of the Sea, ICES Division 4) and off the Scottish west coast (ICES 6a), studies of single nucleotide polymorphic (SNP) markers of spawning cod provide evidence of barriers to gene flow between the deeper north east North Sea region between 100 and 200 m and the shallower shelf region throughout these two stock areas, except for the Clyde Sea (Heath et al, 2014). Genetic isolation of the north east North Sea population is also evident in more recent studies (Sodeland et al, 2016;Fairweather et al, 2018). Analyses of otolith chemistry, comparing larval, juvenile, and adult parts for the same year-class in the North Sea, suggests that this reproductive isolation is maintained by a combination of hydrographical isolation of early life-stages and either fidelity or natal homing of later stages (Wright et al, 2006a(Wright et al, , 2018Svedäng et al, 2010;Neat et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Atlantic cod, Gadus morhua, is well-suited to studying population diversity and reproductive traits as there is already considerable information on both genetic divergence (Bradbury et al, 2013;Barth et al, 2017) and variation in maturity and fecundity (Wright and Rowe, 2019). Like most marine fish the level of genetic differentiation based on unlinked neutral SNPs appears to be very low in Atlantic cod (Bradbury et al, 2013;Berg et al, 2015) with most reported genomic divergence being related to polymorphic chromosomal rearrangements linked to adaptive loci (Bradbury et al, 2013;Berg et al, 2015;Sodeland et al, 2016;Fairweather et al, 2018). However, these genomic regions of adaptive divergence appear very relevant for advising on the appropriate scale for stock management as they appear to reflect reproductive barriers linked to local environmental adaptation and migratory phenotypes (Bradbury et al, 2013;Barth et al, 2017;Kess et al, 2019).…”
Section: Introductionmentioning
confidence: 99%